Energy consumption-economic growth Nexus: An empirical study of China / Ha Junsheng - Ha , Junsheng (2017)
Research on the nexus between energy consumption and economic growth provide important insights that the government needs to design proper policies for the country. However, the existing literature present mixed findings. Therefore, more research that is able to produce more reliable and consistent results are still needed. This study aims to examine the energy consumption and economic growth in China by focusing on the aspects that are usually neglected in the literature such as multiscale causality relationship, nonlinear causality relationship and Asymmetric causality relationship. In order to achieve these objectives, different new research methods will be adopted. The newly proposed linear causality test, nonlinear causality test and asymmetric causality test are applied on the national data. The first two methods fail to capture causality in any direction while the third method identifies causality between positive and/or negative energy and growth shocks. Then the wavelet decomposition technique is combined with these three tests respectively. The result shows that the wavelet decomposition does help reveal the dynamics of the time series in different time horizon, i.e. short, medium and long run. Furthermore, the combination of wavelet decomposition and the asymmetric causality test proves to be able to provide more accurate information on the energy-growth nexus than the other two methods. The newly proposed causality test that uses the bootstrapping method to tackle the small sample issues is applied on the individual regions in China. The test helps identify the characteristics of the energy-growth nexus for individual regions with robust results. Since the development of renewable energy is a growing trend not only in China but also all over the world, the causal relationship between renewable energy consumption and economic growth is examined lastly. Other than contributing in terms of methodology improvement, with all of the empirical results derived from the tests conducted above, this study manages to provide policy recommendations for the Chinese central government in different time horizons and the local governments. In addition, it also sheds light on the renewable energy policy in China.